Calorie labelling on the menu: extent and disparities in use at sit down restaurants in the United States - Mbogori, Teresia N.; Freeland, Kylan B. (International Journal Of Community Medicine And Public Health, 2021)
Background: Obesity remains a major health concern all over the world. The Food and Drug Administration in 2018 enacted a policy that required all food chain restaurants with more than 20 establishments to include calorie information on their menus. Very few studies have assessed the effects of this policy since its enactment. Methods: A secondary data analysis was conducted using the Health Information National Trends Survey (HINTS-5 Cycle 3), a nationally-representative survey administered by the National Cancer Institute (NCI). Data were collected using telephone interviews between January and May 2019. Regression models were used to determine the relationships between demographic and health related variables and the use of calorie information on the menu. Results: Forty six percent of the participants (n=5438) stated that they noticed calorie information on the menu. Among those who noticed the information, 65%, 37% and 44% reported that they ordered fewer calories, fewer items, or smaller sizes respectively, while 4%, 2%, and 2% reported that they ordered more calories, more items or larger sizes. Men were less likely to report seeing calorie information on the menu as compared to women (OR 0.70; CI: 0.56-0.89). Similarly, when compared to those between 18-45 years old, those 75 years and older were 33% less likely to report seeing this information (OR: 0.67 CI: 0.46-0.98). The odds of noticing calorie information on the menu increased with increase in education and income. Conclusions: Gender, age education, and income disparities exist in the use of calorie information among restaurant goers in the US. More targeted education is needed to ensure that the policy attains its intended goal.